Recent Advances in the Development of Macrolide Antibiotics as Antimicrobial Agents - Qin, Yinhui; Ma, Shutao (Mini Reviews in Medicinal Chemistry, 2020)
The chemical modification of natural products has been a major method in the discovery and synthesis of new macrolide antibiotics (MA) to treat a variety of infectious diseases. However, a lot of MA obtained in the above methods are no longer effective, because the bacteria quickly develop their resistance to these new macrolides, which has become a great threat to successful treatment of infectious diseases, such as infections of the respiratory system and urinary system. In this paper, total synthetic methods for MA that include erythromycin A (ERY), azithromycin (AZM), the clinical candidate solithromycin (CEM-101), as well as 14-membered and 15-membered azaketolides have been systematically reviewed on the basis of the literature reported previously. The total synthetic methods we describe here helps to accelerate the discovery of newer MA to deal with the serious problem of bacterial resistance.
Keywords: chemical modification